2012
DOI: 10.1152/ajpregu.00223.2012
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of intrinsic cardiac neurons: effects of β-adrenergic receptor blockade in guinea pig models of chronic heart disease

Abstract: Chronic heart disease induces remodeling of cardiac tissue and associated neuronal components. Treatment of chronic heart disease often involves pharmacological blockade of adrenergic receptors. This study examined the specific changes in neuronal sensitivity of guinea pig intrinsic cardiac neurons to autonomic modulators in animals with chronic cardiac disease, in the presence or absence of adrenergic blockage. Myocardial infarction (MI) was produced by ligature of the coronary artery and associated vein on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Additionally, there was no change in the baseline excitability in neurons from control, MI, and MI with drug treatments. Previous studies demonstrated that chronic MI induces an increased sensitivity to NE in the F/I curves (14). This result was confirmed in the present study ( Fig.…”
Section: Effects Of Ang II Modulators In Healthy Animalssupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, there was no change in the baseline excitability in neurons from control, MI, and MI with drug treatments. Previous studies demonstrated that chronic MI induces an increased sensitivity to NE in the F/I curves (14). This result was confirmed in the present study ( Fig.…”
Section: Effects Of Ang II Modulators In Healthy Animalssupporting
confidence: 93%
“…Previous studies (14) showed that implantation of empty pumps, in either control or sham MI surgery, had no effect on neuronal responses. Intracellular voltage recordings were obtained from individual neurons in whole-mount preparations of the cardiac plexus.…”
Section: Effects Of Ang II Modulators In Healthy Animalsmentioning
confidence: 90%
See 2 more Smart Citations
“…In that study, stimulation was delivered at a moderate intensity (2.0 ± 0.6 mA) and a frequency of 5–10 Hz (near the natural frequency of discharge of vagal fibres during physiological reflex activation24, 25). The device used in the ANTHEM‐HF study (VITARIA, LivaNova PLC, London, UK) received Conformité Europeénne Mark approval in 2015 for the treatment of HFrEF 26…”
Section: Introductionmentioning
confidence: 99%